USULAN MODEL DALAM MENENTUKAN RUTE DISTRIBUSI UNTUK MEMINIMALKAN BIAYA TRANSPORTASI DENGAN METODE SAVING MATRIX DI PT. XYZ - Ririn Rahmawati; Nazaruddin Matondang; Rahmi M Sari (Departemen Teknik Industri Universitas Sumatera Utara, 2014)
Route distribution of a product constituting the order dismissal successive against branches and planning process from point of origin (a company) to the point of consumption (consumers) to fulfill its best customers turn. Pt. Xyz. Is the company in the sectors production snacks. Area their distribution over all the agent scattered in town medan. In medistribusikan of PT. XYZ sued for could design performance shipping reliable, while in fulfillment of a target there are still problems of companies are in distribution products. The process of product distribution in once product delivery only done to one retailing. Distribution products improper in determining route distribution to customers and without seeing former capacity of conveyance resulting in path traveled inefficient. This research berujuan to get route distribution by using centrifugal savings matrix that integrates any muaraangke supply facilities (csf) to distribution canter (d.c.) considering capacity conveyance and means of transportation owned company and to get route distribution efficient with optimize the mileage distribution minimize the use of conveyance; minimizing a charge required by the company and get time distribution feasiable. In distribution system beginning, PT. XYZ send to 14th outlet/day with the mileage 521,600 km and fund of rp. 847.600 and 5 fruit conveyance. By using the method saving matrix produce sub-division route less than route distribution company, applied where sub-division route proposal ' s 7 sub-division routes, produce a greater minimum with thrift distance of 193,7 km can save cost distribution rp. 309.725,- and matrix raise a total time distribution car conveyance of 1193,554 minutes with total car conveyance allocated about three units. Distribution system proposal can save distance of 37,1% and can save the transportation of 36,5 %.